Web-based document certification system with advanced encryption standard digital signature - Henny Indriyawati; Titin Winarti; Vensy Vydia (Institute of Advanced Engineering and Science, 2021)
Web-based degree document certification system with a digital signature in Semarang University has a purpose to support academic to do online document certification through a system. The main problem which occurs in academic administration is a long document certification process that causes an ineffective and inefficient certification process. To solve the problem, a system that can encrypt a document for better security is required. This system is built with the advanced encryption standard algorithm with a 128-bit sized key to encrypt confidential information inside the document. During the encryption process, this algorithm operates using 4x4 bit array blocks and passing many encryption processes for at least 10 (ten) times. The application is analyzed with object-oriented analysis and modeled with Unified modeling language. The result of this research is a system which can secure document with AES algorithm with a 256-bit sized key. The security element in this algorithm will make easier to identify the owner of the document. The secured document is easily accessible through PHP-based web or available QR code. When decrypting the document, the application will activate the camera function and decrypt the information document.